TASK TECHNOLOGY DAN TECHNOLOGY CHARACTERISTICS; TRANSFORMASI MOBILE BANKING BANK MANDIRI FITUR NEW RELEASE LIVIN' BY MANDIRI DAN PENGARUHNYA TERHADAP KEPUASAN SERTA PENGGUNAAN BERKELANJUTAN PADA NASABAH BANK MANDIRI - Safira Safira; Whony Rofianto (Journal of Accounting, Management and Islamic Economics, 2023)
The rapid development of information technolagy has brought changes to ttte financial industry, especially the banking industry with the emergence of mobile banking whiclt rs defihed as a sysfem where cusfomers can conduct banking transactians ihrough applications on smartphones anytime and anywhere. Through this research by developing further research on cantinuance intention in using mobile banking and adding self-efficacy towards mobile banking users with the concept af tasklechnalogy fit (TTF) whictt will explain the relationship between technotogy characteristics and task technology, the purpase of this study is to analyze the effect of tasktechnology fit on customer satisfactian and sustainable use af mobite banking users. Empirical data in this study were collected through surveys that vvere distributecl online via qttestionnaires to Bank Itlandiri customers domiciled rn Jabodetabek who had used the Livin' by lMandiri application for at least 6 months with a tatal sample data of 81 respondents. This research method uses fhe PIS-SEM (Partiall-easf Square Structural Equatian Model) approach ta measure the estimation of the measurement mode! and the estimation of the structural model. The results showed that there was a positive relatianship between technalogy characteristics and tasklechnology fit, and task'-technology fit proved ta have a positive effect on perceived useft//ness and perceived usefulness proved to have a positive effect on satisfaction ancl continuance intention. lVleanwhile, the positive effect of task technology on task-technology fit and the effect of se{f-efficacy an continuance intention has not been proven in this study.